Transforming Acquisitions and Collection Services: Perspectives on Collaboration Within and Across Libraries - Flinchbaugh, Michelle (Charleston Insights in Library, Archival, and Information Sciences, 2019)
This book explores ways in which libraries can reach new levels of service, quality, and efficiency while minimizing cost by collaborating in acquisitions. In consortial acquisitions, a number of libraries work together, usually in an existing library consortia, to leverage size to support acquisitions in each individual library. In cross-functional acquisitions, acquisitions collaborates to support other library functions. For the library acquisitions or technical services manager, or the library director, awareness of different options for effective consortial and cross-functional acquisitions allows for the optimization of staff and resources to reach goals. This work presents those options in the form of case studies, as well as useful analysis of the benefits and challenges of each. By supporting each other’s acquisitions services in a consortium, libraries leverage size to get better prices, and share systems and expertise to maximize resources while minimizing costs. Within libraries, the library acquisitions function can be combined with other library functions in a unit with more than one purpose, or acquisitions can develop a close working relationship with another unit to support their work. This book surveys practice at different libraries, and at different library consortia, and presents a detailed description and analysis of a variety of practices for how acquisitions units support each other within a consortium, and how they work with other library units, specifically collection management, cataloging, interlibrary loan, and the digital repository, in the form of case studies. A final sections of the book covers fundamentals of collaboration.